DARI AIR PANAS KE AIR HIDUP: ANALISIS TEOLOGIS KOMPARATIF 'PADAKANAN' DESA TORAGET DENGAN PERIKOP YOHANES 4:1-42 - Mumu, Andre Shevcenco; Supit, Elma Gabriela (PT. Giat Konseling Nusantara, 2025)
In Toraget Village, Minahasa, the ‘Padakanan’ hot springs serve as a vital center for communal life, yet its potential theological meaning remains unexplored. A gap exists between the communal physical practice around the hot springs and its theological interpretation as